Financial Stress on Academic Performance of Students: A Case of Uganda Christian University - Desire Ainembabazi (Uganda Christian University, 2026)
The study examined the impact of financial stress on academic performance of students: a case of Uganda Christian University (UCU). It specifically focused on; examining the relationship between tuition stress and academic performance of students in UCU, establishing the relationship between living expenses stress and academic performance of students in UCU, and determining the relationship between financial support stress and academic performance of students in UCU. The study was carried out using a cross sectional survey research design where both quantitative and qualitative research approaches were also used. The data was collected using questionnaires and interviews during the data collection, both purposive and simple random sampling methods were used. A sample size of 352 students was meant to be involved in the study although 320 responded. More so 5 key informants who are deans and HODs were used in this study. The study findings established that financial stress significantly affects students’ academic performance at Uganda Christian University, with tuition stress (r = .745**, p < .05), living expenses stress (r = .688**, p < .05), and financial support stress (r = .603**, p < .05) all showing strong and statistically significant relationships with academic outcomes. The findings indicate that challenges related to tuition payment, daily living costs and inconsistent financial support create anxiety, reduce concentration, limit class attendance and participation, and ultimately undermine students’ academic engagement and performance. In conclusion, the study showed that financial stress is a very crucial determinant of student’s academic performance at Uganda Christian University with tuition, living expenses and financial support challenges significantly affecting student’s concentration, engagement in studies and academic outcomes. Lastly, the study recommended that Uganda Christian University strengthen financial aid schemes, provide targeted support for living expenses, promote financial literacy training, create flexible part-time employment opportunities, and enhance counseling services in order to reduce financial stress and improve students’ academic engagement and performance.
Undergraduate